PENGARUH KOMPETENSI TERHADAP KINERJA PEGAWAI NEGERI SIPIL DI BADAN PERENCANAAN PEMBANGUNAN DAERAH KABUPATEN KAMPAR - Hendra, Teguh; Wahyuni, Sri (Sekolah Tinggi Ilmu Ekonomi Riau, 2021)
Human resources are an element and one of the elements that must be paid more attention to by every agency, especially when considering that government agencies are dealing with public services to the community. This forces every agency to be able to work more effectively, efficiently and productively. In carrying out activities or jobs, employees certainly need good skills in completing their work. Therefore, the quality of human resources must always be maintained and improved from the day of their obligation, with the aim of having capable and competent human resources in their respective fields of work. Human resource capabilities can be formed through activities related to their respective fields, such as providing routine training activities for employees in accordance with their respective fields of work. The number of samples in this study were 54 people. From the results of the validity test of the whole statement items between the competency variable and the performance variable were declared valid because the value rcount > rtable (0.268) was obtained. The results of simple linear regression obtained the value of Y = 10,289 + 1,135X. From the results of the partial test or t test, it is obtained that the value of tcount (17,927) > from the value of ttable (2.006) with a significant level of 0.000 < 0.05 means that the competency variable has a significant effect on the performance variable. And the coefficient of determination R2 of 0.861 means that the contribution or magnitude of the influence of competence on performance is 0.861 or 86.1 %, while the remaining 13.9 % is influenced by other variables that are ignored or not examined in this study.